2020
DOI: 10.9770/jesi.2020.8.2(39)
|View full text |Cite
|
Sign up to set email alerts
|

Green economy in Russia: the investments’ review, indicators of growth and development prospects

Abstract: Currently the "green" economy is an important part of positioning in the international arena as an environmental component of sustainable development. Russia, as an active party in the international arena, supports resolutions on the "green" economy development and "green" financing tools for resolving issues of climate-resistant economic growth. Factors and trends in the Russian "green" economy development are radically different from most developed countries. At the same time, Russia has undeniable advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
13
0
6
Order By: Relevance
“…Our study focuses on the case of the Russian Federation -a country where matters of environmental degradation and damage have been left neglected for a long time and which is now facing the urgent need to reduce the anthropogenic pressure on the environment and develop the 'green' economy [10]. Since environment is a complex, multi-faceted research topic, in our study we are going to concentrate on only one of its aspects -air pollution from stationary sources such as power plants and manufacturing facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Our study focuses on the case of the Russian Federation -a country where matters of environmental degradation and damage have been left neglected for a long time and which is now facing the urgent need to reduce the anthropogenic pressure on the environment and develop the 'green' economy [10]. Since environment is a complex, multi-faceted research topic, in our study we are going to concentrate on only one of its aspects -air pollution from stationary sources such as power plants and manufacturing facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Motor vehicles in Kurgan Region are gradually switching to the use of more environmentally friendly gas engine fuel. In December 2019, out of the total number of buses carrying passengers through Kurgan city routes the share of buses operating on methane amounted to 88.1%, which is 7.8% more compared to the previous year (Volodina, 2021). This fact undoubtedly contributes to the reduction of atmospheric air pollution by transport.…”
Section: Research Questionsmentioning
confidence: 99%
“…It supports the conservation of resources, reduces the burden on the ecosystem, contributes to the growth of natural capital, and improves the well-being of the society. The green economy needs to strike a balance between economy, environment and social policy (Merino-Saum et al, 2020;Prudnikova & Mudretsov, 2020;Tarkhanova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The institutional, social, and economic factors underlying environmental degradation have been also explored by researchers in parallel with the international environmental collaborations and the studies have revealed GDP, GDP per capita, sectoral composition, urbanization, financial development, tourism, trade liberalization, FDI inflows, environmental taxes, renewable energy use, energy efficiency, circular economy, recycling, population growth, deforestation, public governance, economic and financial regulations, and the legal system as potential determinants of environmental sustainability [7][8][9][10][11][12][13][14]. In this study, the influence of economic freedom indicators and education on CO 2 emissions is investigated by taking the research gap in the related empirical literature into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have analyzed the effect of many variables including GDP, GDP per capita, sectoral composition, urbanization, financial development, tourism, trade liberalization, FDI inflows, environmental taxes, renewable energy use, energy efficiency, circular economy, recycling, population growth, deforestation, public governance, economic and financial regulations, and legal system on the environment [7][8][9][10][11][12][13][14], but education and economic systems of a country are also very important for the environment because both education and economic freedom have an effect on the environment directly or indirectly through these variables. However, the interaction among education, economic freedom, and the environment has not been sufficiently investigated yet.…”
Section: Introductionmentioning
confidence: 99%